2016
DOI: 10.1002/ange.201603017
|View full text |Cite
|
Sign up to set email alerts
|

A Disposable Planar Paper‐Based Potentiometric Ion‐Sensing Platform

Abstract: Ion-selective electrodes (ISEs) are widely used tools for fast and accurate ion sensing. Herein their design is simplified by embedding ap otentiometric cell into paper, complete with an ISE, areference electrode,and apaper-based microfluidic sample zone that offer the full function of ac onventional ISE setup.T he disposable planar paper-based ion-sensing platform is suitable for low-cost point-of-care and in-field testing applications.T he design is symmetrical and each interfacial potential within the cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Bearing in mind trends in micro-fabrication and nanotechnology, miniaturized ISEs, especially solid-contact microelectrodes, have become a unique tool to investigate in life sciences and environmental monitoring. Also, microfluidic-based analytical devices (mPADs) have emerged as an attractive analytical and detection platform for the development of simple and cost-effective molecular diagnostic assays [90,149]. The integration of mPADs with potentiometric ISEs enables the development of flexible, portable, and inexpensive biosensing devices.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Bearing in mind trends in micro-fabrication and nanotechnology, miniaturized ISEs, especially solid-contact microelectrodes, have become a unique tool to investigate in life sciences and environmental monitoring. Also, microfluidic-based analytical devices (mPADs) have emerged as an attractive analytical and detection platform for the development of simple and cost-effective molecular diagnostic assays [90,149]. The integration of mPADs with potentiometric ISEs enables the development of flexible, portable, and inexpensive biosensing devices.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Paper-based potentiometry lowers costs and makes the construction of chemical sensors more accessible while preserving the analytical performance. Several examples of paper-based potentiometry for decentralized applications have been described during recent years [20][21][22][23][24]. Our group has demonstrated that paper-based sensors for peroxide and biosensors for glucose in whole blood can be successfully developed.…”
Section: Introductionmentioning
confidence: 98%
“…To date, there are only a few examples of fully‐integrated paper‐based ISEs, i. e., devices that require no assembly and take advantage of wicking of the sample into paper to hold the sample. They include paper‐based reference electrodes with a Ag/AgCl/KCl half cell [20] as well as devices with ion‐selective and ionic‐liquid reference membranes embedded into paper, with colloid‐imprinted mesoporous carbon as solid contact [21–23] . Fully‐integrated devices have also been produced with automated ink‐jet printing [24] …”
Section: Introductionmentioning
confidence: 99%